A regard on the thermal comfort theories from the standpoint of Electric Vehicle design — Review and perspectives. (November 2022) - Nastase, Ilinca; Danca, Paul; Bode, Florin; Croitoru, Cristiana; Fechete, Lucian; Sandu, Mihnea; Coşoiu, Costin Ioan
Abstract: In the short and medium term, it is estimated that electric mobility will play an important role in greenhouse gas emissions reduction strategy. However, vehicles with electric propulsion system come with a new series of challenges, some of them affecting more or less the well-being of vehicle users. The purpose of this article is to present in an exhaustive manner a review of data existing in the technical and scientific literature regarding thermal comfort of the passengers in the vehicular ambient, with a perspective on specific issues related to the design of the Electric Vehicles. Firstly, a general outline about the subject area is presented and the aspects of the vehicular environment are discussed. Next, a short introduction in the theories of the human thermal comfort, presenting the physiological bases of thermal comfort and a short discussion of the aspects of the vehicular spaces. The standards currently in use for thermal comfort assessment in vehicles are also discussed in the context of their suitability along other experimental methods for research and development. We will discuss in the final part of the article the particularities of Electric Vehicles and some solutions that are worth to be considered. Compared with buildings indoor environment, the vehicle cabin ambient is very different in terms of thermal comfort parameters magnitude and weight and also due to highly transient condition. The present vehicle standards for thermal comfort are constructed based on the building services standards. In regard to all the aspects presented in the present review, the main conclusion of this article is related to the need to develop specific methods for assessing the thermal comfort, solely for vehicles. Graphical abstract: Highlights: Literature review on 105 publications — thermal comfort of the vehicle passengers. Current vehicle thermal comfort standards are based on the building standards. Need to develop specific methods for assessing the thermal comfort for vehicles. A thermal sensitivity test device was built to perform tests for humans. Perspective on specific issues related to the design of the Electric Vehicles.